Implikasi Yuridis Penyelesaian Perselisihati Hubungan Industrial Melalul Pengadllan Hubungan Industrial - Mila Karmila Adi (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The Industrial Relationship Dispute Resolution Law Number2 Year 2004, has a bolished the existence of The Labor Dispute Committee and replaced by the  Industrial Relation ship Court. The existence of the Industrial Relation ship Court can influence the relation ships here between worker and employer in the future and subtractthe government intervention in labordispute resolution. Although the Court is notexistyet until 2006, but the resolution process will be questioned whether it will give more effectiveness for theboth parties, the worker and the employer, or make more difficulties